2016
DOI: 10.1136/bcr-2016-217454
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids did not reverse type 1 diabetes mellitus secondary to pembrolizumab in a patient with metastatic melanoma

Abstract: Immune checkpoint inhibitors offer patients with advanced melanoma substantial improvements in survival. Unlike chemotherapy, immune checkpoint inhibitors such as ipilimumab and pembrolizumab cause unique immune-related adverse events (irAEs), including the development of endocrinopathies. We report a case of a man aged 60 years who developed diabetic ketoacidosis (DKA) following the use of pembrolizumab for the treatment of metastatic melanoma. He received four cycles of ipilimumab, before proceeding to pembr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 34 publications
1
46
0
5
Order By: Relevance
“…In this case, the diagnosis itself was relatively easy, and we could manage the acute phase of fulminant T1DM and ketoacidosis with sufficient fluid supply, electrolyte correction, and the administration of insulin. Generally, many irAEs can be managed by discontinuing the ICIs or with the use of steroids; these treatments rarely improve endocrine function in cases of hypothyroidism or T1DM . In this case, we did not use steroids as it was irreversible and the condition was manageable with insulin therapy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this case, the diagnosis itself was relatively easy, and we could manage the acute phase of fulminant T1DM and ketoacidosis with sufficient fluid supply, electrolyte correction, and the administration of insulin. Generally, many irAEs can be managed by discontinuing the ICIs or with the use of steroids; these treatments rarely improve endocrine function in cases of hypothyroidism or T1DM . In this case, we did not use steroids as it was irreversible and the condition was manageable with insulin therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Generally, many irAEs can be managed by discontinuing the ICIs or with the use of steroids; these treatments rarely improve endocrine function in cases of hypothyroidism or T1DM. 8,9 In this case, we did not use steroids as it was irreversible and the condition was manageable with insulin therapy.…”
Section: Discussionmentioning
confidence: 98%
“…The use of glucocorticoids was not able to reverse T1DM in a patient treated with pembrolizumab for metastatic melanoma. 45 The proposed mechanism for the development of T1DM is that lower PD-1 expressing CD4+ cells may lead to activation of autoreactive T cells that can infiltrate pancreatic islet cells and ultimately lead to T1DM. 41 It is suspected that high-risk HLA class I and II genotypes may be associated.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…The incidence of immunotherapy‐induced Type 1 diabetes is reported to be ~0.4% ; however, reports suggest that the real‐world incidence may be significantly higher . Cohort studies of islet antibody‐positive people (mainly first‐degree relatives of people with Type 1 diabetes) have found that ~10% with a single positive antibody will progress to Type 1 diabetes .…”
Section: Introductionmentioning
confidence: 99%